Niedoszły zamysł habilitacji ks. Józefa Nowackiego na Wydziale Teologicznym Uniwersytetu Jagiellońskiego w świetle jego listów do ks. prof. Tadeusza Glemmy - Prokop, Krzysztof R. (Ecclesia. Studia z Dziejów Wielkopolski, 2012)
Among Polish Church historians of the past century Fr. Józef Nowacki (1893-1964) holds an eminent position. His opus vitae is a monumental monograph The History of the Archdiocese of Poznań. Another major work in his prolific output is a study titled On the Dignity and Primatial Prerogatives of the Archbishop of Gniezno, which was originally published in Latin in 1937 (the Polish translation appeared only in 2008). The latter monograph became the basis of his habilitation in 1938 at the Faculty of Theology at the Jan Kazimierz University in Lvov. Previously, however, Nowacki considered habilitation at the Faculty of Theology at Jagiellonian University. He was encouraged in this resolve by Fr. Tadeusz Glemma, who like himself came from the diocese of Chełmno (Culm) and attended the same classic high school there. The article provides an account of those endeavors in the light of the correspondence that passed between Nowacki and Glemma. This is a detail which has so far been unknown to historians.